ROLE OF ULTRASONOGRAPHY IN EARLY DIAGNOSIS OF INFANTILE HYPERTROPHIC PYLORIC STENOSIS - Khan, Ashar Ahmad; Yousaf, Muhammad Aslam; Ashraf, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Infantile hypertrophic pyloric stenosis (IHPS) is a common cause of gastric outlet obstruction in infants. This study was conducted to identify the accuracy of ultrasonography in the diagnosis of infantile Hypertrophic pyloric Stenosis. Methods: This cross-sectional descriptive study was conducted in Department of Paediatric Surgery, Children Hospital Complex & the Institute of Child Health, Multan during two year period from 1st July, 2010 to 30th of June, 2012. Fifty patients <8 weeks of age who presented with complaints of non-bilious vomiting were included in the study. Abdominal ultrasound was performed in all the cases. On ultrasonography pyloric canal length, diameter and pyloric muscle wall thickness was measured. Open surgery was performed as per indications and after informed consent. The pre-operative findings were compared with ultrasongraphic findings. Study variable were male to female ratio, percentage of cases in which pyloric mass was palpable. We also compare the duration of onset of symptoms with pyloric canal length, diameter and muscle thickness. Results: In this study, out of 50 patients, 46 (92%) were male and 4 (8%) were females. Gastric peristalsis was visible in 100% patients and mass was palpable in 14 (28%) patients. Pyloric canal length was more than standard in 98% cases; canal diameter was more than the standard in 87% cases and pyloric muscle thickness in 60% of cases. Ultrasonographic findings remained 98% accurate in this study. Conclusion: Ultrasonography is an investigation of choice for early diagnosis of IHPS before significant fluid and electrolyte imbalance occur. It is cost effective, harmless, freely available and easier to perform. Pyloric canal length and diameter are more specific for the diagnosis of IHPS than pyloric muscle thickness. Keywords: Ultrasonography, Infantile hypertrophic pyloric stenosis